A liberdade de gritar: o “veneno como remédio” no processo da educabilidade das paixões no contexto das torcidas organizadas de futebol - Lima, Gustavo Henrique Alves de (2022)
This paper is the result of a theoretical – developed at the Faculty of Education of the Federal University of Goiás, Brazil, within the Graduate Program in Education (Subarea: Culture and Educational Processes) research that sought in general terms to reflect whether the aggressiveness in students who are members of soccer clubs’ Organized Fans in schools necessarily needs to be extirpated. In specific terms, I tried to: analyze the counterpoint made by authors who consider aggressiveness as necessary for the formation of the student, especially the student supporter; find a way to placate the prejudiced speeches that see Organized Fans as something to be extirpated; reflect on the possibility of cohabiting elements that constitute human practices, more precisely aggressiveness and symbolic violence. The hypothesis I defend throughout this paper, suggested in the title, is that the “freedom to shout” comes from aggressive impulses (the need to attack) that can be provoked from the outburst of the passion of self-love. However, instead of extirpating this passion, what can be learned from Rousseau is that it can be worked on as a “remedy”, as long as it is regulated, limited, and allowed within the general rules of coexistence. Thus, limited to the symbolic, it may not be as bad as it seems, as harmful, or something that cannot be “remedied”. The dissertation is, therefore, organized in two parts: Chapter 1 of Part One has Husserl as its epistemological pillar and Chapter 2 has Bourdieu as its focus; Chapter 1 of Part Two seeks to explore more the phenomenon of Organized Fans clubs, with Toledo's anthropological contribution, and Chapter 2 is dedicated to Rousseau, trying to abstract the idea of “poison as a remedy” in order to apply it to the phenomenon studied here. Therefore, it is not about making an apology to unruly behavior, nor to physical violence. On the contrary, the goal is to think of socially allowed means to channel the impulses to symbolically attack and violate, instead of extirpating them. The idea of allowing Organized Fans to also be educational organizations is a demand, an imperative that is posed today. Just as samba schools have their cooperative activities, such as choreographies, building flags, creating anthems, songs, rehearsals, and many other ludic actions, for example, it is possible that the Organized Fans have them as well. In this way, they may serve as parameters to think about fans in the school environment, where the physical educator (and perhaps the education teacher) may be able to use the “poison” (Organized Fans) as a “remedy” through pedagogical action.